A review of bismuth‐based nanoparticles and their applications in radiosensitising and dose enhancement for cancer radiation therapy - Daryoush Shahbazi‐Gahrouei; Yazdan Choghazardi; Arezoo Kazemzadeh; Paria Naseri; Saghar Shahbazi‐Gahrouei (IET Nanobiotechnology)
Abstract About 50% of cancer patients receive radiation therapy. Despite the therapeutic benefits of this method, the toxicity of radiation in the normal tissues is unavoidable To improve the quality of radiation therapy, in addition to other methods such as IMRT, IGRT, and high radiation dose, nanoparticles have shown excellent potential when ionising radiation is applied to the target volume. Recently, bismuth‐based nanoparticles (BiNPs) have become particularly popular in radiation therapy due to their high atomic numbers (Z), high X‐ray attenuation coefficient, low toxicity, and low cost. Moreover, it is easy to synthesise in a variety of sizes and shapes. This study aimed to review the effects of the bismuth‐based NP and its combination with other compounds, and their potential synergies in radiotherapy, discussed based on their physical, chemical, and biological interactions. Targeted and non‐targeted bismuth‐based NPs used in radiotherapy as radiosensitizers and dose enhancement effects are described. The results reported in the literature were categorised into various groups. Also, this review has highlighted the importance of bismuth‐based NPs in different forms of cancer treatment to find the highest efficiency for applying them as a suitable candidate for various cancer therapy and future clinical applications.